Novel biomarkers for pulmonary hypertension in children with ventricular septal defect - Khaled Mahmoud Salem Zayed; Ahmed Mohsen Abdelhakeem; Marwa Elhady; Tarek Abd El Kareim Eldahshan (SpringerOpen, 2016)
Background: Children with congenital heart disease (CHD) who have relevant systemic-to-pulmonary shunts will develop pulmonary hypertension (PH) if untreated. With advances in medical research, new biomarkers representing different physiological processes continue to emerge, providing an ever clearer risk profile for patients with PH. Aim: To evaluate the role of serum galectin-3 and heart fatty acid binding protein (H-FABP) as early predictive biomarkers of PH in children with ventricular septal defect (VSD). Method: The study included 50 children with VSD; 24 of them had PH and 25 age and sex matched healthy children serve as a control group. Serum levels of galectin-3, H-FABP and echocardiography evaluation were done for all cases and control subjects. We investigated the correlation between these markers and pulmonary pressure in children with VSD. Results: Serum levels of galectin-3 and H-FABP were significantly higher in patients with PH. There was a significant positive correlation between both markers and pulmonary pressure. Galectin-3 and H-FABP have 76%, 60% sensitivity and 80%, 96% specificity respectively for prediction of PH in children with VSD. Conclusion: Galectin-3 and H-FABP are promising cardiac biomarker for prediction and risk stratification of PH in children with VSD.